Islam dan Transformasi Sosial Dalam Perspektif Pemikiran Kuntowijoyo - Abdul Aziz Nurizun (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
In this short research the writer wants to see Islam and social transformation based on Kuntowijoyo’s perspectives. He looks at the im- portance of cultural democracy, besides political and economical demo- cracy. He apprehends the symptom of “refeodalization” or “neofeodali- zation” which causes cultural symbols often being used as domination means from the higher structure with mythical sanctions. In this situation Islam comes with its solution i.e collective sentiments in the internal struc- ture of ummah, under something immatery namely faith ‘iman’.